Reconsidering Tonotopic Maps in the Auditory Cortex and Lemniscal Auditory Thalamus in Mice - Tsukano, Hiroaki; Horie, Masao; Ohga, Shinpei; Takahashi, Kuniyuki; Kubota, Yamato; Hishida, Ryuichi; Takebayashi, Hirohide; Shibuki, Katsuei (Frontiers in Neural Circuits, 2017)
The auditory thalamus and auditory cortex (AC) are pivotal structures in the central auditory system. However, the thalamocortical mechanisms of processing sounds are largely unknown. Investigation of this process benefits greatly from the use of mice because the mouse is a powerful animal model in which various experimental techniques, especially genetic tools, can be applied. However, the use of mice has been limited in auditory research, and thus even basic anatomical knowledge of the mouse central auditory system has not been sufficiently collected. Recently, optical imaging combined with morphological analyses has enabled the elucidation of detailed anatomical properties of the mouse auditory system. These techniques have uncovered fine AC maps with multiple frequency-organized regions, each of which receives point-to-point thalamocortical projections from different origins inside the lemniscal auditory thalamus, the ventral division of the medial geniculate body (MGv). This precise anatomy now provides a platform for physiological research. In this mini review article, we summarize these recent achievements that will facilitate physiological investigations in the mouse auditory system.